The use of medicinal plants in the prevention of COVID-19 using the Health Belief Model: A survey based on the Iranian population - Masoomeh Latifi; Fatemeh Maraki; Mohammad-Javad Parvaresh; Mohammadreza Zarei; Leili Allabakhshian (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Because of the spread of coronavirus disease 2019 (COVID-19), the preventive measures have increased, such as focusing on the use of medicinal plants in most communities, including Iran. The purpose of this study was to identify the knowledge, attitude, and performance of individuals toward the use of medicinal plants and to identify the predictors of the use of medicinal plants in the prevention of COVID-19. MATERIALS AND METHODS: This descriptive-analytical study (February-April 2021) was performed on 3840 Iranian men and women aged 20-70 years selected as a multi-stage cluster study. At the first stage, all provinces were divided into five regions: North, South, East, West, and Center. In the second stage, a provincial center and a city were randomly selected from each region (North: Sari, Babol; South: Bushehr, Bandar Genaveh; East: Mashhad, Sabzevar; West: Hamedan, Toisarkan; Center: Yazd, Ardakan). Data were collected by a researcher-made scale based on the Health Belief Model (HBM). Data analysis was performed applying Pearson correlation coefficient, logistic regression, and linear regression. RESULTS: The results showed that people have relatively high knowledge and positive attitude toward the use of medicinal plants in prevention of COVID-19. The most important reason for positive attitude was the perceived benefits with the mean of 75.06%. Also, half of the people had poor performance. Correlation coefficient showed that the use of medicinal plants with perceived sensitivity (p = 0.000, r = 0.3), perceived benefits (p = 0.012, r = 0.126), perceived barriers (p = 0.000, r = 0.179), and perceived self-efficacy (p = 0.000, r = 0.305) had a significant correlation. The strongest correlation between perceived self-efficacy was observed with the use of herbs in prevention of COVID-19. The HBM constructs can predict 26% of the variance for the use of medicinal plants in the prevention of COVID-19, among which perceived self-efficacy (β = 0.230) was the most powerful predictor. CONCLUSION: Based on the results, the predictive role of self-efficacy constructs for the use of medicinal plants in prevention of COVID-19 has been confirmed according to the HBM. Therefore, methods of increasing self-efficacy such as training programs and providing appropriate intervention models can be used not only as promoters of using medicinal plants in prevention of COVID-19 but also for improving people's performance in the proper use of medicinal plants.